Alpine plant communities differ in their seed germination requirements along a snowmelt gradient in the Caucasus - Sergey Rosbakh; Eduardo Fernández-Pascual; Andrea Mondoni; Vladimir Onipchenko (Alpine Botany, 2022)
Mesoscale heterogeneity of alpine landscapes generates snowmelt gradients resulting in a distinct vegetation zonation from almost snow-free fellfields to long-lasting snowbeds. Although the vegetative trait variation along such gradients has been intensively studied, little is known about whether and how seed germination is adapted to the variable snowpack duration. Here, we compare the seed germination niches of 18 characteristic plant species occurring in four distinct plant communities (alpine lichen heath— Festuca varia grassland— Geranium - Hedysarum meadow—snowbed) along an alpine snowmelt gradient in the North Caucasus (Russia). In a fully factorial experiment, we tested seed germination responses to temperature (10/2, 14/6, 18/10, 22/14, 26/18 and 30/22 °C) and water potential (0, − 0.2, − 0.4, − 0.6 and − 0.8 MPa) gradients, reflecting the full spectrum of seedling establishment conditions in the study system. Community-specific germination niches were identified by generalised mixed model with Bayesian estimation. Our study revealed that the species from the four focal communities significantly differed in their temperature requirements for germination, whereas soil moisture was found to be a limiting factor for seedling establishment along the entire gradient. The snowbed germination was constrained to comparatively high temperatures above 10 °C, whereas seed germination in alpine lichen heaths occurred under a wide range of experimental conditions. The seed germination patterns of species from Festuca varia grasslands and Geranium - Hedysarum meadows reflected their intermediate position along the snowmelt gradient. We conclude that seed germination niche is affected by the environmental filtering along the snowmelt gradient thus departing from the general alpine germination syndrome.